Penerapan Massage Effleurage Terhadap Perubahanan Nyeri Pada Pasien Post Sectio Caesarea Di Ruang Ponek Rsud Dr. Soeratno Gemolong - Bonita Dwi Juniana Bahari; Erika Dewi Noorratri; Fitria Purnamawati (STIKes Ibnu Sina Ajibarang, 2024)
Sectio caesarea or commonly called cesarean section is one of the labor procedures to remove the baby through an incision in the abdomen. Central Java is the province with the 3rd highest number of childbirths (9,291) after West Java (15,043) and East Java (9,832). The sectio caesarea rate in Central Java is 17.1% (Ministry of Health, 2019). SC copying causes post-SC pain caused by surgery on the abdominal wall. Objective: To determine the application of message effleurage to pain changes in post sectio caessarea patients in the ponek room of RSUD dr. Soeratno Gemolong. Method: This research uses Case Studies. The research design used by the researchers was the true experimental pre-posttest method Results: there was an effect of massage effleurage on changes in pain of post-sectio caesarea patients in the ponek room of RSUD dr. Soeratno Gemolong. Conclusion: The development of the final results of application to both respondents decreased pain with a mild pain scale which means that the indicator is met.